White matter volume and microstructural integrity are associated with fatigue in relapsing multiple sclerosis - Alejandra Figueroa-Vargas; Sebastián Navarrete-Caro; Claudia Cárcamo; Ethel Ciampi; Macarena Vásquez-Torres; Bernardita Soler; Cristian Montalba; Matías Iriarte-Carter; María Paz Martínez-Molina; Patricio Carvajal-Paredes; Mariana Ayala-Ochoa; Víctor Márquez-Rodríguez; et al. (Scientific Reports)
Abstract Multiple sclerosis (MS) is a prevalent neurological disorder marked by inflammation and demyelination, with fatigue being one of the most reported and debilitating symptoms. While fatigue occurs across various neurological conditions and even in healthy individuals, the specific mechanisms contributing to fatigue in each context remain unclear. In this study, we conducted a cross-sectional analysis involving 32 people with relapsing MS (PwRMS) and 29 healthy controls who reported fatigue. Participants underwent MRI scans, including T1-weighted and diffusion-weighted imaging. Additionally, the Modified Fatigue Impact Scale was utilized. We employed Bayesian LASSO and Spike-and-Slab LASSO regression models to investigate the hypothesis that fatigue correlates differently with brain structures in PwRMS. Our findings revealed brain regions associated with general and cognitive fatigue. In particular, reduced white matter volume and compromised microstructural integrity in specific areas—such as the cingulate gyrus, inferior frontal gyrus, and the banks of the superior temporal sulcus—showed significant associations with fatigue scores in PwRMS. These results suggest that alterations in specific brain regions may play a critical role in the clinical manifestation of fatigue in MS. Understanding these insights could help differentiate general mechanisms of fatigue from those affecting people with relapsing MS, which may guide future therapeutic strategies.